MEANING FROM THE STYLISTIC POINT OF VIEW - Tina Oniani (Scholar Express Journal, 2021)
Research aim is that what is stylistic domain importance of its word, wordcombinations, sentences, and also the manner of expression. The linguistic term ‘meaning’-has been defined in so many ways that there appears an urgent need to clear it. In stylistic meaning also is viewed as a category which is able to acquire meanings-imposed words by the context. In stylistics it is important to discriminate shades or nuances of meaning, but each of meanings, being closely interwoven and interdependent, can none the less be regarded as relatively autonomous and therefore be analysed separately. Words can be classed according to different principles, as there are: a) Morphological –part of speech; b) Semantic-synonims, antonims, thematic; c) Stylistic. and other types of classification. In each of these classifications lexical or grammatical meanings assumed different manifestations.in a morphological classification words are grouped according to their grammatical meaning.in a semantic classification, according to their logical meaning.in a stylistic classification, according to their stylistic meaning
Keywords: Meaning; contextual; polysemanticism; semiotics